Tracking in product delivery using portable RFID with arduine (Research, Society and Development, 2020)
This study aimed to develop a device for traceability of the goods delivery process, using radio frequency technology (RFID), which will inform the date, time and location where the goods are being delivered to the end customer. The methodology used consisted of three stages: 1) data collection through a portable collector along with RFID tags, 2) data processing by the microcontroller and 3) carrying out the consultation of the information contained in the tag through the communication between the RFID and the Arduino, whose product traceability was carried out through radio frequency sending information via GSM; while the materials used were 1 mega arduino board, 1 6m Neo GPS shield, 1 Sim 900 module, 1 RC522 RFID reader, 1 16x2 graphic LCD display and 1 keychain RFID tag. For testing the sending of date, time, product specifications and location information via SMS to the registered cell phone at the time of product delivery, operations were carried out in different locations with different dates and times and the messages were sent without fail. The results confirmed the display of the information “Data Collected Successfully” on the LCD display, after the reading of the LCD label by the collector. The proposed prototype proved to be effective, managing to control the delivery of low-cost goods through passive tag on a portable RFID reader.